Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Siswa SDI Tangkala 1 - Wahyullah Alannasir; Nurhayati Selvi (STKIP Andi Matappa Pangkep, 2021)
One of the efforts made to overcome the low learning outcomes is the selection of the right learning model. The purpose of this study was to determine the application of the Problem Based Learning model and its effect on science learning outcomes for class V SDI Tangkala 1. This research approach was quantitative, the type of experimental research was quasi-experimental design. This research is located at SDI Tangkala 1. The population of class V SDI Tangkala 1 Makassar City is 36 students. The sampling technique used saturated sampling, so the number of samples remained 36 students. Data collection techniques: tests, observations and documentation. Data analysis techniques: Descriptive and inferential statistics. Independent sample T-Test hypothesis test. The results showed that the application of the Problem Based Learning model could be carried out well based on the stages of learning. The results of the study showed that the average value in the experimental group was higher than the control group. There is an effect of the Problem Based Learning model on the science learning outcomes of fifth grade students of SDI Tangkala 1 based on the analysis test stating that the t-count value is greater than the t-table value.